Situation factors in purchasing organic food - Čolović Milica; Mitić Vladimir (Acta Agriculturae Serbica)
Despite the lack of information and the insufficient level of consumer knowledge, the organic food market has recorded constant growth in the last twenty years and has an increasing share in the total food and beverage market. The most common motives of consumers for buying organic food are concern for health, absence of pesticides and chemical agents, concern for animal welfare and environmental protection, better quality of organic food and backup to the local economy. The main goal of this paper is to examine the relationship between certain situational motives and the incidence of buying organic food. The research was conducted in the form of a questionnaire filled out by 400 respondents. The SPSS program version 26 was used to process the collected data. In addition to descriptive statistics, which was used to better represent the sample in the research, non-parametric techniques of the Mann-Whitney U test and the Kruskal-Wallis one-way analysis of variance test were also used. The results showed that factors such as proximity to organic food stores, consumer car ownership and constant internet connection were associated with the frequency of organic food purchases, while factors such as type of working hours and length of employment contract were not. Also, employees in healthcare and education buy organic food products more often than employees in other sectors.